2014
DOI: 10.1002/mame.201400224
|View full text |Cite
|
Sign up to set email alerts
|

Altering the Trigger‐Behavior of Programmed Shape Memory Natural Rubber (SMNR) by Solvent Vapor

Abstract: Lightly cross‐linked natural rubber was found to have a tunable trigger‐temperature through programming procedure. Solvent vapor has a further impact on the trigger‐behavior of programmed SMNR. For exploring this we used the 1st derivative of the temperature dependent thickness increase to get insights in the trigger‐behavior. Additionally subsequently applied solvent vapor treatment allows reversibly changing TTrig as well as the maximum trigger‐rate νmax and thus the whole trigger‐process. The variation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…Besonders interessant ist dabei, dass die Triggertemperatur dieser Probe in der Regel deutlich höher ist als die der ursprünglich programmierten, lösungsmittelunbehandelten Probe. Folglich sind Lösungsmitteldämpfe offensichtlich auch dazu einsetzbar, um eine bereits programmierte Triggertemperatur ohne Neuprogrammierung signifikant zu verändern 22,23. Durch eine solche Lösungsmittelbehandlung lassen sich sogar Naturkautschuk‐Vulkanisate mit Vernetzungsgraden oberhalb von 0,4 Prozent programmieren, die über konventionelle Kalt‐ oder Heißprogrammierung keinen Formgedächtniseffekt bei Raumtemperatur aufweisen würden 16…”
Section: Lösungsmittelsensorik Mit Formgedächtnis‐naturkautschukunclassified
“…Besonders interessant ist dabei, dass die Triggertemperatur dieser Probe in der Regel deutlich höher ist als die der ursprünglich programmierten, lösungsmittelunbehandelten Probe. Folglich sind Lösungsmitteldämpfe offensichtlich auch dazu einsetzbar, um eine bereits programmierte Triggertemperatur ohne Neuprogrammierung signifikant zu verändern 22,23. Durch eine solche Lösungsmittelbehandlung lassen sich sogar Naturkautschuk‐Vulkanisate mit Vernetzungsgraden oberhalb von 0,4 Prozent programmieren, die über konventionelle Kalt‐ oder Heißprogrammierung keinen Formgedächtniseffekt bei Raumtemperatur aufweisen würden 16…”
Section: Lösungsmittelsensorik Mit Formgedächtnis‐naturkautschukunclassified
“…Detailed studies revealed that solvent vapors can be efficiently applied not only for increasing the trigger temperature of SMNR after programming but also for discretizing its trigger process . To this end, SMNR is firstly cold‐programmed, which results in a relative low trigger temperature but extremely narrow trigger range beneath 1 K. Secondly, the strain of the programmed SMNR is kept constant while exposing the constraint SMNR to a suited solvent.…”
Section: Solvent‐aided Programming Of Smnrmentioning
confidence: 99%
“…Detailed studies revealed that solvent vapors can be efficiently applied not only for increasing the trigger temperature of SMNR after programming but also for discretizing its trigger process. 70,71 To this end, SMNR is firstly coldprogrammed, which results in a relative low trigger temperature but extremely narrow trigger range beneath 1 K. Secondly, the strain of the programmed SMNR is kept constant while exposing the constraint SMNR to a suited solvent. This way, T trig can be increased by 10 K while maintaining a narrow trigger range of less than 1 K. Furthermore, such solvent treatment enables programming even of NR vulcanizates with degrees of cross-linking above 0.4% that cannot be programmed conventionally to trigger temperatures above room temperature (see Fig.…”
Section: Solvent-aided Programming Of Smnrmentioning
confidence: 99%
“…Actually, they are capable of exceeding by far well‐established SMAs. Examples are diverse trigger options (heat, pH, chemicals, mechanical stress, UV/IR, electric/magnetic fields), tunable trigger temperatures, narrow trigger ranges, cold programmability, extremely large stored strains, multishape memory, shape memory‐assisted self‐healing, and even heating rate sensitivity . However, the trigger temperatures of most SMPs are considerably lower compared to those of SMAs, which are known for trigger temperatures of more than 700 °C .…”
Section: Introductionmentioning
confidence: 99%